2010
DOI: 10.1111/j.1750-3841.2010.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Tritiated Liquids by Individual Breakfast Cereal Flakes

Abstract: Surface liquid adhesion (SLA) and liquid absorption (LA) of tritiated liquids, including water and skim, low-fat, whole, and fat-enriched milks, by cornflakes (CF) and frosted flakes (FF) were determined by scintillation counting using water-[(3)H] at 0.5 microCi/mL. SLA or the liquid adhering to individual flakes after a short immersion period was the same for CF and FF in the case of water (approximately 0.011 microL mm(-2) of flake) but were always higher for CF than for FF and increased as the fat content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Data and models showed that the RF for BFP was lower when the flake was immersed in water than in milk. Sacchetti and others (2003) and Medina and others (2010) have suggested that during immersion in whole milk it is possible that a layer of lipids and casein micelles is deposited on the flake's surface, which hinders liquid transfer into the interior, thus, retarding softening of the matrix. In the case of QF, it is suggested that the sugar coating is probably responsible for the slower transition during the initial part of the soaking period as it occurred with the quantification of milk absorption in frosted flakes (Medina and others 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data and models showed that the RF for BFP was lower when the flake was immersed in water than in milk. Sacchetti and others (2003) and Medina and others (2010) have suggested that during immersion in whole milk it is possible that a layer of lipids and casein micelles is deposited on the flake's surface, which hinders liquid transfer into the interior, thus, retarding softening of the matrix. In the case of QF, it is suggested that the sugar coating is probably responsible for the slower transition during the initial part of the soaking period as it occurred with the quantification of milk absorption in frosted flakes (Medina and others 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The approach of analyzing individual food units in spite of their structural variability has been successfully validated in deep‐fat frying of potato strips where the relative contributions of surface and structural oil to total oil uptake during frying are now well documented (Bouchon and Aguilera 2001). Medina and others (2010) studied the uptake of tritiated liquids by individual BCF showing that measurements in bulk overestimate the amount of liquid “absorbed” by the mass of flakes. Most of the difference corresponds to interstitial liquid occluded between the flakes that do not drain before weighing the mass of flakes.…”
Section: Introductionmentioning
confidence: 99%
“…Surface liquid adhesion and liquid absorption of milk with different fat contents and distilled water by the matrix of individual corn and frosted flakes (FF) were quantified using liquids in their titrated form. This showed that surface and internal characteristics play an important role in the liquid transport through and inside the flake structure (Medina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%